Read: my life through books - Privat, Brooke, author (Colorado State University. Libraries, 2024)
What we as people read influence our lives in many ways. Through the examination of psychological and social science literature as well as my own life experiences, I uncover some of these impacts. Our beliefs, interests, and even career paths can be shaped by books. Not only did I demonstrate this to readers, but I also discovered it for myself. Through reading many memoirs and writing my own personal narrative, I learn and write about the universality of many human experiences and gain empathy and understanding for people with different stories.
University Honors Program.
Keywords: psychology; read; books; development; interests; career; memoir